2008
DOI: 10.1111/j.1863-2378.2007.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Cysticercosis in Cattle Slaughtered at Awassa Municipal Abattoir, Ethiopia: Prevalence, Cyst Viability, Distribution and its Public Health Implication

Abstract: A cross-sectional study was conducted from October 2005 to April 2006 on bovine cysticercosis in cattle slaughtered at Awassa municipal abattoir with the objective of determining the prevalence of Taenia saginata cysticercosis, cyst viability, distribution and its public health implication. Questionnaire survey involving 120 respondents was also conducted on human taeniasis. A total of 400 carcasses were examined during the study period, of which 105 (26.25%) were infected with T. saginata metacestodes. From a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
54
7
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 7 publications
15
54
7
5
Order By: Relevance
“…Slaughter inspection for Cysticercus bovis, based on 'eye and knife' meat inspection, finds at most between 10% to 20% of the cases if proper inspection is done. Macpherson et al [28,29] when doing proper inspection of predilection sites, found that cysticercosis was detected in 10.5% of slaughtered cattle in different abattoirs in Tanzania, with Arusha having the highest proportion of 16.7% and Morogoro the lowest with 6.5% [30] . Heart muscle and musculus triceps brachii harbored the highest numbers of cysts [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Slaughter inspection for Cysticercus bovis, based on 'eye and knife' meat inspection, finds at most between 10% to 20% of the cases if proper inspection is done. Macpherson et al [28,29] when doing proper inspection of predilection sites, found that cysticercosis was detected in 10.5% of slaughtered cattle in different abattoirs in Tanzania, with Arusha having the highest proportion of 16.7% and Morogoro the lowest with 6.5% [30] . Heart muscle and musculus triceps brachii harbored the highest numbers of cysts [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Bovine cysitcercosis is widely distributed in Ethiopia and a number of individual reported the prevalence of bovine cysitcercosis in different parts of the country 2.25% reports of Tembo (3.2%) and (2.9% and 4.4%) prevalence Jimma in south-western Ethiopia (Megersa et al; Tolosa et al) and Ziway (3.0%) (Bedu et al) in southern Ethiopia and (26.3%) (Abunna et al) in Hawasa and in north-western Ethiopia (18.5%) (Kebede) [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand the contribution of Cysticercus bovis to organ condemnation in slaughtered cattle at different abattoir have been reported [12,13]. It is a great problem in developing country like Ethiopia due to the cultural habit eating raw meet as routine dish and holidays has promoted human taeniasis in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Para se estimar a dimensão destas perdas, na África anualmente perde-se de 1 a 2 bilhões de dólares devido a cisticercose, que apresenta uma prevalência em torno de 10 a 30% (Harrison 1996;Opara et al, 2006;Abunna et al, 2008;Kebede et al, 2008;Kebede, 2008). Na Europa a prevalência é de 0,01 a 6,8% de acordo com a SCVPH (2000), mas estima-se que seja ainda maior devido a falhas no sistema de notificação .…”
unclassified
“…Assim, a inspeção visual das carcaças é o método mais eficiente para detecção da carne contaminada com cisticercos, apesar de apenas 10 a 20% dos cistos serem identificados na linha de inspeção habitual (Berends et al 1993).…”
unclassified